2018
DOI: 10.1128/aac.02583-17
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Pseudomonas aeruginosa Aminoglycoside Mutational Resistome In Vitro and in the Cystic Fibrosis Setting

Abstract: Inhaled administration of high doses of aminoglycosides is a key maintenance treatment of chronic respiratory infections in cystic fibrosis (CF). We analyzed the dynamics and mechanisms of stepwise high-level tobramycin resistance development and compared the results with those of isogenic pairs of susceptible and resistant clinical isolates. Resistance development correlated with mutations and mutations, conferring polymyxin resistance, were also frequently selected In contrast, mutational overexpression of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 34 publications
0
55
0
Order By: Relevance
“…To examine if the precise mutations found in our in vitro study were also found in clinical isolates, we searched published genomes of P. aeruginosa clinical isolates from cystic fibrosis patients who had likely been treated with aminoglycosides like TOB (Bolard et al, 2017; Chung et al, 2012; López-Causapé et al, 2017, 2018; Markussen et al, 2014). We identified fusA1 and ptsP mutations in these genomes, suggesting that these mutations evolve during infections.…”
Section: Resultsmentioning
confidence: 99%
“…To examine if the precise mutations found in our in vitro study were also found in clinical isolates, we searched published genomes of P. aeruginosa clinical isolates from cystic fibrosis patients who had likely been treated with aminoglycosides like TOB (Bolard et al, 2017; Chung et al, 2012; López-Causapé et al, 2017, 2018; Markussen et al, 2014). We identified fusA1 and ptsP mutations in these genomes, suggesting that these mutations evolve during infections.…”
Section: Resultsmentioning
confidence: 99%
“…We used PROVEAN to assess the frequency of likely change-of-function mutations in isolates of P. aeruginosa from patients. For comparison we analysed a panel of isolates from the general environment (Table 2) A high proportion of clinical isolates contained likely function-altering differences in genes that are established as contributing to clinical resistance to fluoroquinolones (gyrA and parE), carbapenems (mexR, nalD) and/ or aminoglycosides (mexY, amgS) (Table2) (27,28,(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evolution of antibiotic-resistant mutants from sensitive parent strains, followed by whole genome sequencing to identify resistance-conferring mutations, is an approach that has been applied to a number of species (16)(17)(18)(19)(20)(21), including P. aeruginosa (22)(23)(24)(25)(26)(27)(28). Studies have confirmed the involvement of genes previously proposed to be associated with resistance in P. aeruginosa.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Particularly relevant is the activity of chromosomally-encoded multidrug-resistance (MDR) efflux pumps (10, 11). Further, the acquisition of mutation-driven resistance is common in this opportunistic pathogen, particularly along chronic infections (1214), where the constitutive overexpression of MDR efflux pumps is one of the biggest problems to eradicate these infections (10, 15, 16). Efflux pumps exhibit different functions, with physiological and ecological significances that go beyond their activity as antibiotic resistance elements (10, 1719).…”
Section: Introductionmentioning
confidence: 99%